Mechanical loading of bone-anchored implants during functional performance tests in service members with transfemoral limb loss - Gladish, Jonathan R.; Dearth, Christopher L.; Beachler, Mark D.; Potter, Benjamin K.; Forsberg, Jonathan A.; Hendershot, Brad D. (Frontiers in Rehabilitation Sciences, 2024)
For individuals with limb loss, bone-anchored implants create a direct structural and functional connection to a terminal prosthesis. Here, we characterized the mechanical loads distal to the abutment during several functional performance tests in Service members with transfemoral (TF) limb loss, to expand on prior work evaluating more steady-state ambulation on level ground or slopes/stairs. Methods: Two males with unilateral TF limb loss and two males with bilateral TF limb loss participated after two-stage osseointegration (24 and 12 months, respectively). Tri-directional forces and moments were wirelessly recorded through a sensor, fit distal to the abutment, during six functional tests: Time Up and Go (TUG), Four Square Step Test (FSST), Six Minute Walk Test (6MWT), Edgren Side-Step Test (SST), T-Test (TTEST), and Illinois Agility Test (IAT). Additionally, participants performed a straight-line gait evaluation on a 15m level walkway at a selfselected speed (0.93-1.24 m/s). Peak values for each component of force and moment were extracted from all six functional tests; percent differences compared each peak with respect to the corresponding mean peak in straight-line walking. Results: Peak mechanical loads were largest during non-steady state components of the functional tests (e.g., side-stepping during SST or TTEST, standing up from the ground during IAT). Relative to walking, peak forces during functional tests were larger by up to 143% (anterior-posterior), 181% (medial-lateral), and 110% (axial); peak moments were larger by up to 108% (flexion-extension), 50% (ab/adduction), and 211% (internal/external rotation).A more comprehensive understanding of the mechanical loads applied to boneanchored implants during a variety of activities is critical to maximize implant survivability and longterm outcomes, particularly for Service members who are generally young at time of injury and return to active lifestyles.